The maternal health outcomes of paid maternity leave: A systematic review. (April 2015) - Aitken, Zoe; Garrett, Cameryn C.; Hewitt, Belinda; Keogh, Louise; Hocking, Jane S.; Kavanagh, Anne M.
Abstract: Paid maternity leave has become a standard benefit in many countries throughout the world. Although maternal health has been central to the rationale for paid maternity leave, no review has specifically examined the effect of paid maternity leave on maternal health. The aim of this paper is to provide a systematic review of studies that examine the association between paid maternity leave and maternal health. We conducted a comprehensive search of electronic databases (Medline, Embase, CINAHL, PsycINFO, Web of Science, Sociological Abstracts) and Google Scholar. We searched websites of relevant organisations, reference lists of key papers and journals, and citation indices for additional studies including those not in refereed journals. There were no language restrictions. Studies were included if they compared paid maternity leave versus no paid maternity leave, or different lengths of paid leave. Data were extracted and an assessment of bias was performed independently by authors. Seven studies were identified, with participants from Australia, Sweden, Norway, USA, Canada, and Lebanon. All studies used quantitative methodologies, including cohort, cross-sectional, and repeated cross-sectional designs. Outcomes included mental health and wellbeing, general health, physical wellbeing, and intimate partner violence. The four studies that examined leave at an individual level showed evidence of maternal health benefits, whereas the three studies conducting policy-level comparisons reported either no association or evidence of a negative association. The synthesis of the results suggested that paid maternity leave provided maternal health benefits, although this varied depending on the length of leave. This has important implications for public health and social policy. However, all studies were subject to confounding bias and many to reverse causation. Given the small number of studies and the methodological limitations of the evidence, longitudinal studies are needed to further clarify the effects of paid maternity leave on the health of mothers in paid employment. Highlights: 7 studies were included in the review examining the association between paid maternity leave and maternal health. Studies included participants from Australia, Sweden, Norway, USA, Canada, and Lebanon. The review provides evidence of maternal health benefits of paid maternity leave. Longitudinal studies are needed to better answer this research question.